Kajian Instrumentasi dan Organologi Gendang Beleq Sanggar Mertaq Mi Lombok Tengah Nusa Tenggara Barat - Gde Agus Mega Saputra (Institut Seni Indonesia Surakarta, 2020)
It is of absolute importance, to maintain the art of Gendang Beleq when it comes to its sustainability among the Sasak culture. Therefore, being the identity of Lombok Island in West Nusa Tenggara, the awareness of the people possessing such art is highly demanded, in order to safeguard its advancement. It means that when people do not realize that Gendang Beleq is an asset or representation of their culture, there are many uncertainties regarding the future of its existence. The most obvious thing is the lack of reference related to the explanation of the names of the instruments contained in this art, as well as the organology of Gendang Beleq that has never been published in the form of research journals and books. This paper is more of an effort to explore and understand the existence of each instrument in the Gendang Beleq ansamble group. To capture the value of knowledge and overall description related to Gendang Beleq's art in order to obtain data as desired, the time of the research is conducted using a qualitative approach. Organological studies are used to understand or explore the essence of the presence of each instrument. The researcher as the main instrument was in direct contact with the object of study. Various efforts such as in-depth interviews, documentation, direct involvement in art activities, and conducting in-depth dialogues with actors in this case are carried out to obtain thorough information related to the object of study.